1999
DOI: 10.2307/2641182
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Leaf-Miner Abundance in Elevated CO 2 : Reduced Leaf Quality and Increased Parasitoid Attack

Abstract: Abstract. Most studies on the effects of elevated CO 2 have focused on the effects on plant growth and ecosystem processes. Fewer studies have examined the effects of elevated CO 2 on herbivory, and of these, most have examined feeding rates in laboratory conditions. Our study takes advantage of an open-top CO 2 fertilization study in a Florida scrub-oak community to examine the effects of elevated CO 2 on herbivore densities, herbivore feeding rates, and levels of attack of herbivores by natural enemies.Highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 27 publications
2
46
0
Order By: Relevance
“…Holton et al (2003) found that elevated CO 2 concentrations had no impact on the performance of Compsilura concinnata (Meigen). Similarly, the mortality of different leafminer species associated with parasitism under elevated CO 2 was not significantly different from that observed under ambient CO 2 conditions (Stiling et al 1999). All of these cited studies demonstrate the major variability in parasitoid performance under elevated CO 2 conditions.…”
Section: Atmospheric Changes Affect Interactions With Natural Enemiesmentioning
confidence: 76%
“…Holton et al (2003) found that elevated CO 2 concentrations had no impact on the performance of Compsilura concinnata (Meigen). Similarly, the mortality of different leafminer species associated with parasitism under elevated CO 2 was not significantly different from that observed under ambient CO 2 conditions (Stiling et al 1999). All of these cited studies demonstrate the major variability in parasitoid performance under elevated CO 2 conditions.…”
Section: Atmospheric Changes Affect Interactions With Natural Enemiesmentioning
confidence: 76%
“…The expected concentration of CO 2 in the year of 2100 ranges from 540 to 970 ppm compared to about 280 ppm in the pre-industrial era (Stiling et al 1999), and changes in plant quality due to elevated CO 2 may affect herbivory patterns and insect richness, abundance and/ or diversity. Many studies have now addressed effects of CO 2 enrichment on herbivores mediated by changes in host plant characteristics and how herbivores respond to these altered conditions (reviewed by Stiling & Cornelissen 2007).…”
Section: Eff Ects Of Elevated Co 2 On Plant Chemistry and Herbivore Pmentioning
confidence: 99%
“…We estimated G. elliottii annual aboveground production as the annual flux of G. elliottii mass collected in litter traps (Stiling et al, 1999(Stiling et al, , 2002(Stiling et al, , 2009). Litter of G. elliottii was sorted and measured separately beginning in 1999; in 1997 and 1998, G. elliottii litter fall was measured together with other "non-oak" species.…”
Section: Symbiotic N 2 Fixation By Galactia Elliottiimentioning
confidence: 99%
“…From 2000 to 2006, litter of the oaks and of G. elliottii was scored for damage by insect herbivores and sorted, counted, and weighed separately by species and insect damage category as described previously (Stiling et al, 1999(Stiling et al, , 2009. The rate of litterfall of herbivore-damaged leaves, L (g m −2 year −1 ), was determined for each species as the total mass of damaged litter divided by the area of the litter traps in each chamber.…”
Section: Herbivorymentioning
confidence: 99%